2019
DOI: 10.1016/j.dld.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Expression of long non-coding RNA ANRIL predicts a poor prognosis in intrahepatic cholangiocarcinoma

Abstract: Background: Intrahepatic cholangiocarcinoma (iCCA) is a deadly cancer worldwide associated with an increased incidence, limited therapeutic options and absence of reliable prognostic biomarkers. Long non-coding RNAs (lncRNA) emerge as relevant biomarkers in cancer being associated with tumor progression. However, lncRNA have been poorly investigated in iCCA. Aim: To identify lncRNA significantly associated with the survival of patients with iCCA after tumor resection for curative intent. Methods: Gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“… 8 Even, one kind of long noncoding RNA may be a prognosis biomarker in several tumors concurrently, such as CDKN2B-AS1 (ANRIL) which is a poor prognosis biomarker in intrahepatic cholangiocarcinoma, hepatocellular carcinoma, or uterine corpus endometrial carcinoma. 9 LINC00460 was reported to be associated with poor prognosis of several cancers, such as lung squamous cell carcinoma, 10 colorectal cancer, 11 breast cancer. 12 LINC00460 has been screened to be associated with the overall survival of ccRCC patients, but its prognostic value and effect on cellular function in ccRCC have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Even, one kind of long noncoding RNA may be a prognosis biomarker in several tumors concurrently, such as CDKN2B-AS1 (ANRIL) which is a poor prognosis biomarker in intrahepatic cholangiocarcinoma, hepatocellular carcinoma, or uterine corpus endometrial carcinoma. 9 LINC00460 was reported to be associated with poor prognosis of several cancers, such as lung squamous cell carcinoma, 10 colorectal cancer, 11 breast cancer. 12 LINC00460 has been screened to be associated with the overall survival of ccRCC patients, but its prognostic value and effect on cellular function in ccRCC have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, as a systematic anatomic-based classification, the TNM stage provides a method to estimate cancer prognosis (Huang and O'Sullivan, 2017). Recently, with the development of precision medicine, accumulating evidence demonstrated that lncRNAs possess a potential predictive value in cancer prognosis (Angenard et al, 2019;Li et al, 2019;Xu et al, 2019). Thus, it was shown that the prognostic model generated by combining lncRNAs with TNM stage provides higher predictive ability compared to currently available prognostic systems.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has been confirmed in multiple gastrointestinal cancers but not in cholangiocarcinoma [42]. However, lncRNAs such as PVT1 [43], UCA1 [44], and ANRIL [45], which have been verified to be induced by hypoxia in gastrointestinal cancers [41,42], were also abnormally expressed in CCA, suggesting that further exploration of hypoxia-regulated lncR-NAs in CCA should be carried out.…”
Section: Regulators Of Lncrnas In Ccamentioning
confidence: 93%